2003
DOI: 10.1080/0144361031000119475
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric hysterectomy: fifteen years' experience in a Nigerian tertiary centre

Abstract: The aim of this study was to determine the incidence, indications, associations and complications of obstetric hysterectomy in our centre with a view to suggesting ways of improving outcome. This is a descriptive study of patients who had obstetric hysterectomy in the University of Benin Teaching Hospital from January 1986 to December 2000. Data obtained from hospital records were analysed using appropriate computer statistical software for graphs and chi(2) test. In the period under study there were 20 344 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 4 publications
3
36
4
Order By: Relevance
“…The study showed an association between increasing age and increasing parity with increasing incidence rate of peripartum hysterectomy. It identified age more than or equal 30 years and parity more or equal to four as risk factors for peripartum hysterectomy and this has been reported in West Africa 2,19 .…”
Section: Discussionmentioning
confidence: 76%
“…The study showed an association between increasing age and increasing parity with increasing incidence rate of peripartum hysterectomy. It identified age more than or equal 30 years and parity more or equal to four as risk factors for peripartum hysterectomy and this has been reported in West Africa 2,19 .…”
Section: Discussionmentioning
confidence: 76%
“…In the developing world, preventable factor such as uterine rupture or uterine atony are the most common indication for peripartum hysterectomy [4][5][6][7]9,10,13,14,16]. The common causes of uterine rupture in this part of the world include prolonged obstructed labour, rupture of a previous caesarean scar, injudicious use of oxytocics and trauma from instruments or manual removal [3,4,6,11,17,18]. If the rupture is extensive and hemorrhage cannot be controlled by uterine repair, then hysterectomy may become necessary [17].…”
Section: Discussionmentioning
confidence: 99%
“…The common causes of uterine rupture in this part of the world include prolonged obstructed labour, rupture of a previous caesarean scar, injudicious use of oxytocics and trauma from instruments or manual removal [3,4,6,11,17,18]. If the rupture is extensive and hemorrhage cannot be controlled by uterine repair, then hysterectomy may become necessary [17]. Ours findings confirm this assertion with uterine rupture and uterine atony as main indications of obstetric hysterectomy respectively 63% and 21.7%.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to results obtained from centers in Nigeria and other developing countries. [19,20] Studies from developed countries have found placenta praevia and morbidly adherent placenta as the most frequent indications. [21,22] The difference may be due to the increasing caesarean section rate, improved obstetric care, reduced parity and effective family planning and health policies in the developed countries.…”
Section: IIImentioning
confidence: 99%